Implementation Of Problem Based Learning Method In Islamic Religious Education Subjects In Improving Student Understanding At Darut Taqwa High School - Nisa, Khoirun; Sholikhudin, Muhammad Anang (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
The direction of this research is to explore the dynamics of the implementation of the Problem Based Learning (PBL) approach as it is learned in Islamic Religious Education (PAI), as well as to examine the extent to which this approach affects the level of student understanding in the Darut Taqwa High School environment. This research is based on a descriptive qualitative paradigm, with data collection techniques that include participatory observation, in-depth interviews, and document analysis as the main instruments. The participants include PAI teachers and high school students. The results of the study indicate that the use of the PBL method is able to increase students' active participation, hone their critical thinking skills, and deepen their understanding of religious materials. The success of the implementation of PBL is supported by the readiness of teachers, the availability of adequate learning media, and the motivation of students to learn. However, there are still obstacles such as limited time and inequality in students' ability to work with groups.